The Impact of Menopausal Symptoms on Quality of Life, Productivity, and Economic Outcomes - Whiteley, Jennifer (Mary Ann Liebert, Inc., 2013)
BACKGROUND: The aim of this study was to investigate the impact of menopausal symptoms and menopausal symptom severity on health-related quality of life (HRQoL), work impairment, healthcare utilization, and costs. METHODS: Data from the 2005 United States National Health and Wellness Survey were used, with only women 40–64 years without a history of cancer included in the analyses (N=8,811). Women who reported experiencing menopausal symptoms (n=4,116) were compared with women not experiencing menopausal symptoms (n=4,695) on HRQoL, work impairment, and healthcare utilization using regression modeling (and controlling for demographics and health characteristic differences). Additionally, individual menopausal symptoms were used as predictors of outcomes in a separate set of regression models. RESULTS: The mean age of women in the analysis was 49.8 years (standard deviation,±5.9). Women experiencing menopausal symptoms reported significantly lower levels of HRQoL and significantly higher work impairment, and healthcare utilization than women without menopausal symptoms. Depression, anxiety, and joint stiffness were symptoms with the strongest associations with health outcomes. CONCLUSIONS: Menopausal symptoms can be a significant humanistic and economic burden on women in middle age.